(untitled) (SAARC Journal of Agriculture, 2017)
A field experiment was carried out at Sher-e-Bangla Agricultural University (SAU) Farm during July to November 2011 to evaluate the effect of integrated nutrient management (INM) on T. Aman rice (cv. BRRI dhan40). The field belongs to Red Brown Terrace soil under Tejgoan series having silt loam texture and 6.0 pH. Application of 70 % NPKS fertilizers + 4 t ha-1 dhaincha (Sesbania rostrata) (T1) produced the highest grain yield (5.90 t ha-1), the second highest yield (5.85 t ha-1) was obtained from 80% NPKS + 2 t ha-1 dhaincha (T2) treatment. The grain yield increased by 31.2 to 86.3% over control depending on the treatments. Treatments T1 and T2 resulted in higher N, P, K and S uptake by rice. The N, P, K and S concentrations of rice grain was higher for the treatments where Sesbania and cow dung were together applied in combination with NPKS fertilizers. The combined application of chemical fertilizers and organic manure increased organic carbon (OC), total N, available P, K and S contents in post-harvest soil. The overall results indicate that the integrated use of chemical fertilizer and organic manure can help increase grain yield of rice without deteriorating soil fertility. SAARC J. Agri., 15(1): 43-53 (2017)